(untitled) (Global Journal of Management and Business Research, 2018)
This research concentrates on supply chain practices and its impact on supply chain performance of peanut chikki industry. The aim of this study to analyse the supply chain performance by using various constructs. By using the questionnaire survey the supply chain practices of peanut chikki industry in Kovilpatti was analysed. Survey was conducted directly in their consecutive firms in Kovilpatti. The respondents are the people who are suppliers of the peanut chikki industry in and around Kovilpatti. The nodes and linkages of supply chain are also determined. At the end of study outcomes were discussed with the available data and the suitable interpretation was done and suggestions are put forth setting a path for future studies.